Gender differences in the presentation and management of patients with severe aortic stenosis at specialist versus primary/secondary care centres: a sub-analysis of the IMPULSE enhanced registry - Bleiziffer, Sabine; Messika-Zeitoun, David; Steeds, Rick; Appleby, Clare; Delgado, Victoria; Eltchaninoff, Helene; Gebhard, Catherine; Hengstenberg, Christian; Wojakowski, Wojtek; Frey, Norbert; Kurucova, Jana; Bramlage, Peter; et al. (International journal of cardiology, 2025)
Background - Management and treatment of severe aortic stenosis (AS) may differ considerably in European countries. To investigate these differences in France, Germany, and the UK, the IMPULSE enhanced registry was established. Previous data revealed differences in how patients were managed in specialist (hub) versus primary/secondary care (satellite) centres. - Methods - The IMPULSE enhanced registry sub-analysis aimed to determine if there were gender-specific differences for patients with severe AS at centres with and without access to intervention. - Results - Among the 790 patients, 594 and 196 were recruited at hub and satellite centres, respectively; 44 % of patients were female. In both settings, women were older than men (hubs: 78.7 vs. 76.2, p = 0.007; satellites: 79.8 vs. 75.1, p = 0.002). Symptoms at the presentation were comparable. Males had more often undergone previous cardiac surgery. Females had a smaller left ventricular (LV) outflow tract, smaller LV cavities, and, more often, a preserved ejection fraction (>50 %). There was no gender-based difference in time to intervention. At one year, the cumulative incidence of aortic valve replacement in females was higher than in males in hubs (p = 0.012) but not in satellites (p = 0.600); surgical AVR was more common in males in hubs only (p = 0.008), while transcatheter aortic valve implantation was more common in females in both settings (hubs: p < 0.001; satellites: p = 0.022). One-year survival was comparable in both genders, regardless of setting. - Conclusions - A better understanding of gender-specific differences in patients with severe AS, according to the diagnostic setting, could improve patient stratification and earlier diagnosis.